Energy transfer chemiluminescence for ratiometric pH imaging. Issue 22 (22nd May 2018) - An, Weiwei; Mason, Ralph P.; Lippert, Alexander R.
Abstract : Ratiometric chemiluminescence enables quantitative imaging of pH at precise spatial locations independent from probe concentration and reaction kinetics. Abstract : Chemiluminescence imaging offers a low background and high sensitivity approach to imaging analytes in living cells and animals. Intensity-based measurements have been developed, but require careful consideration of kinetics, probe localization, and fluctuations in quantum yield, all of which complicate quantification. Here, we report a ratiometric strategy for quantitative chemiluminescence imaging of pH. The strategy relies on an energy transfer cascade of chemiluminescence emission from a spiroadamantane 1, 2-dioxetane to a ratiometric pH indicator via fluorescent dyes in Enhancer solutions. Monitoring the pH-dependent changes in chemiluminescence emission at multiple wavelengths enables ratiometric imaging and quantification of pH independent from variations due to kinetics and probe concentration.